2010
DOI: 10.1111/j.1471-4159.2010.06901.x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Hydroxybutyrate and the GABAergic footprint: a metabolomic approach to unpicking the actions of GHB

Abstract: Gamma-hydroxybutyrate is found both naturally in the brain and self-administered as a drug of abuse. It has been reported to act at endogenous γ-hydroxybutyrate (GHB) receptors and GABA(B) receptors [GABA(B)R], and may also be metabolized to GABA. Here, the metabolic fingerprints of a range of concentrations of GHB were measured in brain cortical tissue slices and compared with those of ligands active at GHB and GABA-R using principal components analysis (PCA) to identify sites of GHB activity. Low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 87 publications
2
38
0
Order By: Relevance
“…Our finding is supported by several studies, indicating a possible role for GHB at extrasynaptic α4-containing GABA A receptors. A study using metabolic fingerprinting recently reported that the actions of GHB are similar to several ligands acting at extrasynaptic GABA A receptors (25). A link between GHB and α4 has also been indicated by the ability of GHB to antagonize increases in α4 mRNA levels induced by ethanol withdrawal (24) and the association of chronically elevated GHB levels seen in succinic semialdehyde dehydrogenase KO mice with increased tonic inhibition at extrasynaptic GABA A receptors (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is supported by several studies, indicating a possible role for GHB at extrasynaptic α4-containing GABA A receptors. A study using metabolic fingerprinting recently reported that the actions of GHB are similar to several ligands acting at extrasynaptic GABA A receptors (25). A link between GHB and α4 has also been indicated by the ability of GHB to antagonize increases in α4 mRNA levels induced by ethanol withdrawal (24) and the association of chronically elevated GHB levels seen in succinic semialdehyde dehydrogenase KO mice with increased tonic inhibition at extrasynaptic GABA A receptors (23).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies infer a role for GHB at extrasynaptic GABA A receptors, such as a correlation between elevated GHB levels and increased tonic extrasynaptic inhibition through GABA A receptors (23). More specifically, effects involved receptor subtypes containing α4-and δ-subunits (24)(25)(26).…”
mentioning
confidence: 99%
“…In this study, the microdialysis probe placement was in the frontal cortex for sampling after intravenous GHB administration. The frontal cortex was used to assess GHB toxicokinetics because GABA b receptors [a likely site of action for GHB (Mathivet et al, 1997;Nasrallah et al, 2010)] are highly expressed in the cerebral cortex (Bowery et al, 1987). In addition, GABA concentrations can be measured in the frontal cortex, and a previous report indicated a reduction in GABA release in the frontal cortex after the subcutaneous administration of ␥-butyrolactone, a precursor of GHB (Hu et al, 2000).…”
Section: Brain Uptake Of Ghbmentioning
confidence: 99%
“…The properties of dependence/tolerance and behavioural effects of GHB seem to be consistent with the involvement of the GABAergic receptors, mostly the GABA B R [61,86,87]. GHB activates the GABA B R directly or indirectly through the metabolic conversion of GHB to GABA and the GHB-mediated feedback control of GABA release [21,67]. Subtypes of the GABA B R (subunits GABA B1 and GABA B2 ) are important in mediating the effects of GHB [21,88,89,90,91,92].…”
Section: Neurobiological Pathway Of Ghb Dependencementioning
confidence: 97%
“…Nevertheless, the exact involvement of GHBR is still unclear. The effects of GHB on sleep, as has been suggested, have to be mediated by the β 1 -subunit containing the α 4 -GABA A receptor (GABA A R) [65,66] which is highly sensitive to low concentrations of GHB (levels of 1.0 µ M GHB or below in neuronal level); when the concentration increases an additional GABA A R δ-subunit would putatively become involved [66,67]. In summary, GHB ingested in low doses could initiate some physiological effects mediated mainly by GHBR, the β 1 -subunits of α 4 -GABA A R. These effects which have positive therapeutic functions may unfortunately provide a potential risk for abuse.…”
Section: Endogenous and Exogenous Ghbmentioning
confidence: 99%